Emergency admissions across the transition from paediatric to adult care: cross-sectional analysis of English hospital data. (13th November 2015) - Wijlaars, Linda P M M; Hardelid, Pia; Woodman, Jenny; Cheung, Ronny; Allister, Janice; Gilbert, Ruth
Abstract: Background: Transition from paediatric to adult health services is often sub-optimally achieved for children with long-term conditions. We investigated trends in emergency admissions across the transition from paediatric to adult care. Methods: Using Hospital Episodes Statistics data, we analysed 1 186 392 emergency admissions between April 1, 2009, and March 31, 2012, in children and young people aged 10–24 years. We calculated emergency admission rates for this cohort before (10–15 years), during (16–18), and after transition (19–24) using mid-year population estimates as denominators. We stratified analyses by underlying long-term conditions, which we defined by validated International Classification of Diseases 10th revision codes. We excluded injury-related and maternity-related admissions. We used negative binomial regression to determine incidence rate ratios (IRRs). Findings: Prevalence rates for emergency admissions increased 64% for girls (29/1000 before transition to 48/1000 after transition) and 17% for boys (26/1000 to 31/1000). This increase overwhelmingly occurred during transition (16–18 years), when rates increased 4·0/1000 per year for girls and 2·3/1000 for boys. At the same time, average length of hospital stay increased from 2·1 to 2·9 days for girls, and 1·8 to 5·0 days for boys (increases of 38% and 186% for girls and boys, respectively). Disparities in admission rates increased during transition, with children and young people from the most deprived quintile more likely than those from the least deprived quintile to have an emergency admission (IRR 1·63, 95% CI 1·60–1·66), and more so than before transition (1·51, 1·45–1·56). The increase in admission rates was driven by underlying long-term conditions: overall, rates increased 14% (IRR 1·14, 95% CI 1·13–1·14), but for children and young people with long-term conditions rates increased 46% (1·46, 1·46–1·47). Rates increased most rapidly for mental health problems, metabolic and endocrine disorders, multiple long-term conditions (both sexes), and respiratory disorders (girls only). Interpretation: Our results show that emergency admission rates, duration, and inequalities increase across transition, especially in children and young people with underlying long-term conditions. The extent to which this increase is due to transition within the health service, rather than other developments, requires further research. Our results are in keeping with the widely recognised difficulties that young people face when they transition to adult health services. Funding: LPMMW and JW were supported by funding from the Department of Health Policy Research Programme through funding to the Policy Research Unit in the Health of Children, Young People and Families (grant reference 109/0001). RG is supported by awards establishing the Farr Institute of Health Informatics Research at University College London Partners from the Medical Research Council and a consortium of funders (MR/K006584/1).